ORE TRAPS IN THE MAGMATIC SULFIDE FORMATION - Malyshev A.I. (My University, 2004)
Different ore traps describe together with migration sulfide ores span the entire spectrum of large and superlarge accumulations of magmatic sulfide deposits. Hence, the proposed concept of sulfur condensation in the course of endogenic fluid migration can be used for prospecting, exploration, and revised exploration of the magmatic sulfide deposits.